Proceedings of the 2008 International Conference on Quantitative InfraRed Thermography 2008
DOI: 10.21611/qirt.2008.12_09_16
|View full text |Cite
|
Sign up to set email alerts
|

Defect detection in fiberglass reinforced epoxy composite pipes reproducing field inspection conditions

Abstract: Many works that adopt active thermography as a non-destructive inspection method use very sophisticated equipment for test piece thermal excitation and data acquisition, which demand highly prepared operators, causing their application in industrial environments very costly. This paper aims at detecting defects in adhesive joints of fiberglass reinforced epoxi pipes by means of the Fourier transform phase angle analysis of the time evolution pixel amplitude, using simple and low-cost equipment. Results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…There are two approaches that could be successfully exploited for this purpose, namely PT and LT. [17][18][19] Beside these two established techniques, an indigenously developed method, known as FMTWI 20 may also be employed. In FMTWI, the material surface heating is neither a pulse nor a single frequency, but a linear upchirp whose bandwidth spans over the frequencies necessary to produce thermal diffusion lengths to cover the entire range of defect depths in question.…”
Section: Principle Of Fmtwimentioning
confidence: 99%
“…There are two approaches that could be successfully exploited for this purpose, namely PT and LT. [17][18][19] Beside these two established techniques, an indigenously developed method, known as FMTWI 20 may also be employed. In FMTWI, the material surface heating is neither a pulse nor a single frequency, but a linear upchirp whose bandwidth spans over the frequencies necessary to produce thermal diffusion lengths to cover the entire range of defect depths in question.…”
Section: Principle Of Fmtwimentioning
confidence: 99%
“…Despite this fact, many issues arise when this technique is used in specific applications, especially about the analysis and interpretation of thermographic sequence, or its Fourier transform. In particular, industrial pipelines are an important field of application of NDT techniques, and various specific studies on this subject can be found in the open literature [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this fact, many issues arise when this technique is used in specific applications, especially about the analysis and interpretation of thermographic sequence, or its Fourier transform. In particular, industrial pipelines are an important field of application of NDT techniques, and various specific studies on this subject can be found in the open literature [2][3][4].In this paper, some preliminary experiments have been carried out to evaluate how a variation of specimen orientation affects the test, taking into account directional emissivity, out-of-focus effects and uneven thermal excitation; then this knowledge is applied in a test of a hollow emicylindrical (half pipe) polymethylmethacrylate sample, analyzed with the depth retrieval procedure developed in our laboratory. …”
mentioning
confidence: 99%